North Korean human rights : activists and networks / edited by Andrew Yeo, The Catholic University of America, Danielle Chubb, Deakin University, Victoria. - Yeo, Andrew, 1978-; Chubb, Danielle L. (Cambridge University Press, 2018)
The evidentiary weight of North Korean defectors' testimony depicting crimes against humanity has drawn considerable attention from the international community in recent years. Despite the attention to North Korean human rights, what remains unexamined is the rise of the transnational advocacy network, which drew attention to the issue in the first place. Andrew Yeo and Danielle Chubb explore the 'hard case' that is North Korea and challenge existing conceptions of transnational human rights networks, how they operate, and why they provoke a response from even the most recalcitrant regimes. In this volume, leading experts and activists assemble original data from multiple language sources, including North Korean sources, and adopt a range of sophisticated methodologies to provide valuable insight into the politics, strategy, and policy objectives of North Korean human rights activism.